2016
DOI: 10.1176/appi.ps.201400586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Health Parity on High Utilizers of Services: Pre-Post Evidence From a Large, Self-Insured Employer

Abstract: Federal mental health parity legislation is likely to increase utilization of mental health services by individuals who had previously met their benefit limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…regarding outpatient MI utilization. 17 Our result of increased per-user inpatient BH utilization suggests a roughly similar story to that of McGinty et al, though via a different mechanism: the latter study found increases in the probability of any inpatient OON SUD service use among users of SUD services, 16 and our study found increases in the number of days of inpatient treatment among users of inpatient care. To our knowledge there are no peer-reviewed studies reporting significant changes to plan spending or intermediate care use.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…regarding outpatient MI utilization. 17 Our result of increased per-user inpatient BH utilization suggests a roughly similar story to that of McGinty et al, though via a different mechanism: the latter study found increases in the probability of any inpatient OON SUD service use among users of SUD services, 16 and our study found increases in the number of days of inpatient treatment among users of inpatient care. To our knowledge there are no peer-reviewed studies reporting significant changes to plan spending or intermediate care use.…”
Section: Discussionsupporting
confidence: 84%
“…16 Grazier et al found an association between MHPAEA and increases in outpatient mental health service use among high utilizers, but only studied data from one employer, and only considered changes between 2009 and 2010. 17 …”
Section: Introductionmentioning
confidence: 99%
“…These trends may be related to enhanced mental health coverage in recent years after parity legislation, which may also explain greater continuity in treatment in more recent years. 42 However, these findings need to be corroborated in future studies, especially with regard to increased inpatient treatment that was most prominent in 2014.…”
Section: Discussionmentioning
confidence: 95%
“…Among the general population, there is some evidence of modest utilization increases associated with MHPAEA. Examining the effects of MHPAEA among high-utilizers at one employer group, Grazier et al found an association between MHPAEA and increases in outpatient mental health service use (Grazier, Eisenberg, Jedele, & Smiley, 2015). Two additional studies documented modest increases in expenditures and utilization among all patients enrolled in carve-in plans, which administer both BH and medical benefits (Harwood et al, 2017) and carve-out plans, those that administer only BH benefits (Ettner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%